As If Already Free Anthropology and Activism After David Graeber - High, Holly (Pluto Press, 2023)
A highly original thinker' - New York Times David Graeber (1961-2020) was an American anthropologist and anarchist activist, who left us with new ways to understand humankind. This collection of new writing brings together his insights into one book, showing how deeply his work continues to influence us today. Graeber's writing resonates with both scholars and activists looking to shake things up. The impact of his work is broad in scope, from birth to banking, and he picks open social hierarchy and political power to expose what really makes human society tick. In today's neoliberal world, we can turn to his legacy to provide a way for us to understand what went wrong, and how to fix it. This collection of writings is both an introduction to his life and works, a guide to his key ideas, and an inspiring example of of how anthropologists are continuing to use his work today.